Tren Penelitian Second Language Acquisition di Era Teknologi Digital - Judijanto, Loso (Eastasouth Institute, 2025)
This study analyzes the trend of Second Language Acquisition (SLA) in the era of digital technology with a bibliometric approach using data from Scopus and VOSviewer software. The results show a significant increase in the number of SLA-related publications, reflecting global attention to second language learning. Digital technologies such as learning apps, social media and data analytics have become key elements in supporting language learning innovation, creating more flexible and personalized approaches. Bibliometric visualizations identified key authors, leading countries, and dominant themes such as language learning, linguistics, and multilingualism. However, the study also found gaps in the representation of learners from diverse socio-cultural backgrounds as well as the integration of technology with established SLA theories. This study emphasizes the need for a more inclusive and evidence-based approach in future SLA research, to address global challenges in language learning.